Storms - Pielke, Roger (Ed.); Pielki, Roger (Ed.) (London Routledge, 1999)
Storms are fundamental to life on earth.But their impacts on society are not welcome. While storms bring the rains which make life possible,when extreme,they can take life as well.Worldwide,the societal impacts of storms are measured by lives lost and eco
Keywords: Storms